Ultrasonographic appearance of supraspinatus and biceps tendinopathy improves in dogs treated with low-intensity extracorporeal shock wave therapy: a retrospective study - Kern, Tari; Manfredi, Jane; Tomlinson, Julia (Frontiers in Veterinary Science, 2023)
Objective This study aimed to determine whether dogs with shoulder tendinopathy diagnosed via musculoskeletal ultrasound would show improvement in imaging after treatment using piezoelectric shockwave therapy and rest. Methods Medical records were reviewed for dogs diagnosed with biceps and/or supraspinatus tendinopathy via musculoskeletal ultrasound, treated using piezowave shockwave, and re-imaged post-treatment. Data collected included patient signalment, duration and grade of lameness, prior rest, piezowave dose, and patient outcome, including a return to sport where applicable. Images were scored using an adapted ultrasound grading scale, in addition to obtaining cross-sectional area measurements. Statistics included Shapiro–Wilk tests (normality), Wilcoxon matched pairs signed rank tests (pre- vs. post-treatment comparisons), and Spearman's correlation coefficients (lameness grade vs. ultrasound score) (significant at P < 0.05). Results In total, 26 of 30 dogs had pathology involving both the biceps and supraspinatus tendons in one limb, with 27 of 30 having tendon/s affected bilaterally. For both tendons, post-treatment cross-sectional area and ultrasound score were significantly lower than pre-treatment (P < 0.001). Lameness decreased clinically (P < 0.0001) following piezowave shockwave treatment regardless of the tendons involved, but the lameness score did not correlate with the ultrasound score for either tendon. Conclusion Dogs with tendinopathy of the biceps brachii and supraspinatus showed significant improvement on follow-up musculoskeletal ultrasound and lameness evaluation after the treatment of their tendons using piezoelectric shockwave therapy with rest. Clinical significance Canine biceps brachii and supraspinatus tendinopathy can cause variable lameness and ultrasonographic appearance, which improves after shockwave therapy and rest. The ultrasound scoring system and cross-sectional area assessment provide useful outcome measures for clinical cases.